COMPARATIVE EVALUATION OF ORTHODONTIC TREATMENT OF CLASS 2 ANOMALIES IN CHILDREN WITH MIXED BITE - Kuranbaeva Dilkhumor Gayratovna (Web of Journals Publishing, 2023)
Distal malocclusion is the only type of malocclusion that requires urgent treatment as soon as possible before maxillary discrepancy occurs. The incidence in the population varies around 45%, depending on age, racial group and types of distal malocclusion studied. We studied the frequency of occurrence of distal occlusion and its varieties among 20 children and adolescents with dental anomalies aged 6-13 years. Determining the types of such a complex anomaly as distal occlusion allows for more thorough treatment planning and positive, lasting results.
Keywords: anomaly, distal occlusion, comparative assessment, myobrace, elastopositioner, twin block, bracket system.